2020
DOI: 10.3390/plants9101285
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Tolerant Phenomena, Sequencing and Characterization of a Glyoxalase I (Jojo-Gly I) Gene from Jojoba in Comparison with Other Glyoxalase I Genes

Abstract: Plant response to salt stress and the mechanism of salt tolerance have received major focus by plant biology researchers. Biotic stresses cause extensive losses in agricultural production globally, but abiotic stress causes significant increase in the methylglyoxal (MG) level of GlyoxalaseI (Gly I). Identification of salt-tolerant genes when characterizing their phenotypes will help to identify novel genes using polymerase chain reaction (PCR) to amplify the DNA coding region for glyoxalase I. This method is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In addition, the highest number of shoots and leaves and plantlet fresh weight was also noted in plantlets grown in the 2000 ppm multiple-shoot induction media. These observations were consistent with numerous previous reports [24][25][26][27]. Repeated subculturing in the fresh multiple-shoot induction media with the same salinity was expected to improve all multiplication and growth parameters, as shown by the data presented in Table 2B.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the highest number of shoots and leaves and plantlet fresh weight was also noted in plantlets grown in the 2000 ppm multiple-shoot induction media. These observations were consistent with numerous previous reports [24][25][26][27]. Repeated subculturing in the fresh multiple-shoot induction media with the same salinity was expected to improve all multiplication and growth parameters, as shown by the data presented in Table 2B.…”
Section: Discussionsupporting
confidence: 92%
“…Fayek et al [25] have reported that jojoba plantlets grown at 2000 ppm salinity have the highest average shoot length. Similarly, Mohasseb et al [26] also documented that moderate salinity indeed enhances the shoot length of jojoba plantlets. In fact, in the present study, plantlets that were cultured onto 2000 ppm multiple shoot induction media produced the longest shoots among all salinity treatments (Table 2A).…”
Section: Discussionmentioning
confidence: 79%
“…Obesity, overweight, and insulin resistance are interrelated components of the Metabolic Syndrome (MetS). Indeed, in a recent study on MS the onset of MetS was observed in 22% of patients and insulin resistance in 46% with a higher incidence in comparison with healthy controls [60,61]. Although the association between MetS or insulin resistance and degree of disability has not been unequivocally demonstrated, it has been observed that insulin resistance can exacerbate MSrelated conditions as well as neurocognitive dysfunction and inflammatory and immune responses [62].…”
Section: Malnutrition In Msmentioning
confidence: 99%
“…SRY gene-walking strategy and PCR conditions were adjusted based on our previously reported protocol on papaya and protocols mentioned in other studies ( Solliman et al, 2019 , Mohasseb et al, 2020 , Dominguez and Lopez-Larrea, 1994 ). Mastermix containing DreamTaq DNA Polymerase (Thermo Scientific) was prepared by following the instructions of the manufacturer.…”
Section: Methodsmentioning
confidence: 99%